Elucidation of nanoscale features and antimicrobial activity of Yashad and Vanga Bhasmas - Rajchal, Bimal; Thapa, Mr. Yub Narayan; Karki, Deepshikha; Bhatta, Dr. Pramod; Sharma, Dr. Motee Lal; Adhikari, Prof. Rameshwar (BIBECHANA, 2026)
AbstractYashad Bhasma (YB) and Vanga Bhasma (VB) are traditional Ayurvedic zinc-based and tin-based formulations, respectively, enriched with therapeutic values. Despite their long history, their scientific validation, physicochemical features, and antimicrobial activity are, however, less explored. This study aims to prepare these Bhasmas by following the traditional method described in the Ayurvedic text “Rasashastra” and evaluating their physicochemical and antimicrobial features. Ultraviolet-visible spectroscopy (UV-vis), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Raman spectroscopy, Scanning electron microscopy coupled with energy dispersive X-ray analysis (SEM-EDX), and Transmission electron microscopy (TEM) were used to evaluate the physicochemical and morphological features. The analyses confirmed the crystalline wurtzite zinc oxide structures of YB agglomerated in a circular fashion with an average particle size distribution of 21.3 nm and rutile tin oxide structures of VB agglomerated in flower-like fashion with an average particle size distribution of 38.5 nm. The antimicrobial activity of both Bhasmas was evaluated against wound pathogens B. subtilis and S. epidermidis using the agar well diffusion method. The macro-broth dilution method was used to assess their minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). YB showed 11.00 mm and 11.34 mm zone of inhibition (ZOI) against B. subtilis and S. epidermidis, respectively and MBC of 12.5 – 2.5 mg.mL-1 against both pathogens. The findings provide evidence for the nanoscale features and antimicrobial potential of Ayurvedic Bhasmas, supporting their therapeutic values.